2007
DOI: 10.1111/j.1572-0241.2007.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Celiac Disease in Primary Care: A Multicenter Case-Finding Study in North America

Abstract: This study demonstrates that an active case-finding strategy in the primary care setting is an effective means to improve the diagnostic rate of CD in North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
1
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(161 citation statements)
references
References 38 publications
7
144
1
9
Order By: Relevance
“…This may have resulted in an overestimate of the prevalence of celiac disease in some patient groups however rates of celiac disease in different patient cohorts are similar to previous case finding studies reported in the literature. [27][28][29] Furthermore this increased prevalence did allow us to accrue significant numbers of patients with USCD to allow for effective comparison of patient phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted in an overestimate of the prevalence of celiac disease in some patient groups however rates of celiac disease in different patient cohorts are similar to previous case finding studies reported in the literature. [27][28][29] Furthermore this increased prevalence did allow us to accrue significant numbers of patients with USCD to allow for effective comparison of patient phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore included data from the fully published paper (26), in lieu of the abstract data (58). There were another 4514 subjects identified in 14 studies (16,17,26,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69) from the previous meta-analysis, of whom 2406 met diagnostic criteria for IBS. In total, therefore, the 36 studies recruited 15,256 individuals, of whom 9275 (60.8%) met diagnostic criteria for IBS.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of these studies were identified in the previous literature search (16,17,26,(59)(60)(61)(63)(64)(65)(66)(67)(68)(69), with the remaining 19 studies identified in the updated search (25, 37-42, 44-48, 50, 51, 53-57). The pooled prevalence of a positive EMA and/or tTG was 2.6% (95% CI 1.6% to 3.8%) ( Table 2), but with significant heterogeneity between studies (I 2 = 89.5%, P < 0.001).…”
Section: Yield Of Ema And/or Ttg Testing In Suspected Ibsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,14 Widespread availability of accurate serology for CD facilitates case-finding noninvasively. 15,16 The tissue transglutaminase (tTGA) test is sensitive (>90%) and specific (∼95%) for CD, while endomysial (EMA) test has a variable sensitivity (75-90%) but high specificity (100%). 17,18 Testing both antibodies may improve detection rate.…”
Section: Introductionmentioning
confidence: 99%